Sovereign emergencies: Latin America and the making of global human rights politics / Patrick William Kelly. - Kelly, Patrick William, 1984- (Human rights in history., 2018)
The concern over rising state violence, above all in Latin America, triggered an unprecedented turn to a global politics of human rights in the 1970s. Patrick William Kelly argues that Latin America played the most pivotal role in these sweeping changes, for it was both the target of human rights advocacy and the site of a series of significant developments for regional and global human rights politics. Drawing on case studies of Brazil, Chile, and Argentina, Kelly examines the crystallization of new understandings of sovereignty and social activism based on individual human rights. Activists and politicians articulated a new practice of human rights that blurred the borders of the nation-state to endow an individual with a set of rights protected by international law. Yet the rights revolution came at a cost: the Marxist critique of US imperialism and global capitalism was slowly supplanted by the minimalist plea not to be tortured.